Mixed Convection Heat Transfer in a Vertical Saturated Concentric Annulus Packed with a Metallic Porous Media (Journal of Engineering, 2015)
Mixed convection heat transfer in a vertical concentric annulus packed with a metallic porous media and heated at a constant heat flux is experimentally investigated with water as the working fluid. A series of experiments have been carried out with a Rayleigh number range from Ra=122418.92 to 372579.31 and Reynolds number that based on the particles diameter of Red=14.62, 19.48 and 24.36. Under steady state condition, the measured data were collected and analyzed. Results show that the wall surface temperatures are affected by the imposed heat flux variation and Reynolds number variation. The variation of the local heat transfer coefficient and the mean Nusselt number are presented and analyzed. An empirical correlation has been proposed for computing the Nusselt number for the geometry and boundary conditions under investigation.